VgrG2 of type VI secretion system 2 of Vibrio parahaemolyticus induces autophagy in macrophages - Yu, Ying; Fang, Lihua; Zhang, Yan; Sheng, Hongxia; Fang, Weihuan (Frontiers in Microbiology, 2015)
Type VI secretion system (T6SS) is a macromolecular transenvelope machine encoded within the genomes of several proteobacteria species. Vibrio parahaemolyticus contains two putative T6SS systems, VpT6SS1 and VpT6SS2, both contributing to adherence to Caco-2 and/or HeLa cells. However, it remains unknown if these systems are involved in cellular responses. In order to exclude the effects of other virulence factors known to induce cytotoxicity or autophagy, a triple deletion mutant dTTT (with deletion of tdh, and T3SS1 and T3SS2 structural protein genes) was used as the parent strain to construct deletion mutants of T6SS genes. The mutant dTTT-icmF2, but not dTTT-icmF1, reduced autophagic response upon 4 h of infection of the macrophage. Further attempt was made to search for the possible effector proteins that might be responsible for direct induction of autophagy by deletion of the genes encoding Hcp2 and VgrG2, two putative translocons of T6SS2 of V. parahaemolyticus. Deletion of either hcp2 or vgrG2 did reduce the autophagic response. However, increased LC3-II lipidation was seen only in the macrophage cells transfected with pVgrG2, but not with pHcp2. Chloroquinine treatment increased accumulation of LC3-II, suggesting that VgrG2 enhanced autophagic flux. The fact that vgrG2 deletion led to reduced level of intracellular cAMP suggests a possible role of cAMP signaling in autophagic responses to the bacterium. We conclude that VgrG2 of V. parahaemolyticus induces autophagy in macrophages.